Identification Of Three Key Factors Contributing To The Aetiology Of Dark Circles By Clinical And Instrumental Assessments Of The Infraorbital Region - Mac-Mary S; Zornoza Solinis I; Predine O; Sainthillier JM; Sladen C; Bell M; O'Mahony M (Clinical, Cosmetic and Investigational Dermatology, 2019)
Sophie Mac-Mary,1 Itziar Zornoza Solinis,2 Océane Predine,1 Jean-Marie Sainthillier,1 Christelle Sladen,2 Mike Bell,2 Mark O’Mahony2 1Skinexigence, Besançon, France; 2Walgreens Boots Alliance, Nottingham, UKCorrespondence: Sophie Mac-MarySkinexigence SAS, 2 Rue Paul Milleret, 25000, Besançon, FranceTel +33 3 81 88 95 51Email smac@skinexigence.comBackground: The aetiology of infraorbital dark circles is complex and multi-factorial. The aim of this research was to measure and characterize dark circles and to determine the physiological changes associated with the occurrence of this aesthetically unpleasing issue.Materials and methods: Clinical, photographic and instrumental assessments were performed on Caucasian skin to determine the most appropriate methodologies to measure dark circles, comparing different zones of the infraorbital region in subjects with and without dark circles. Exploratory studies were also carried out on African and Far East Asian skin, as well as on tracking the natural variation of dark circles over seven days in Caucasian subjects.Results: Under-eye dark circles in Caucasian subjects are characterized by significantly darker coloured skin and higher colour deviations between the dark circle region and surrounding areas of skin. Multispectral image analysis produced a higher melanin index in subjects with dark circles, suggesting hyperpigmentation in the affected area, in addition to a higher haemoglobin index. The higher haemoglobin index, combined with preliminary assessments of the vascular network by videocapillaroscopy, suggests there may be more dilated, thicker or increased numbers of capillaries in subjects with dark circles. Ultrasound analysis showed a significant difference in skin thickness between the two groups of subjects linking the appearance of dark circles to thinner skin under the eye. Many of these trends were also observed in African and Far East Asian skin. The results also showed intra-individual, intra-day and inter-day variability of dark circle intensity in subjects with Caucasian skin.Conclusion: Three key physiological factors associated with the occurrence of infraorbital dark circles are hyperpigmentation, a tendency for more dilated, thicker or increased number of capillaries and thinner skin in the under-eye area. The combination of these three factors provides a robust indication of the presence of infraorbital dark circles.Keywords: dark circles, infraorbital, ultrasound imaging, image processing, multispectral imaging, pigmentation